Er fagordbøger et praktisk anvendeligt værktøj? - Gubba, Wilhelm (HERMES - Journal of Language and Communication in Business, 1989)
An analysis of the requirements legitimately and necessarily imposed by practical users of LSP dictionaries and a critical account of the various instances in which compilers often fail to observe these requirements. The article hightlights the basic criteria recommended for successful compilation to achieve maximum utility and reliability of reference, including i.a. considerations in respect of arrangement, fullness of treatment, exemplification, cross-references where applicable, and indisputable exactness thus ensuring that the dictionary becomes a valuable tool in the process of solving complex bilingual problems. In the last section the author recommends the establishment of a general, multi-purpose reference work at national level comprising both LSP language and common language elements. The difficulties of establishing such a project are appraised and possible solutions suggested.